Deployable Telescopic Tubular Mechanisms With a Steerable Tongue Depressor Towards Self-Administered Oral Swab - Kumar, Kirthika Senthil; Nguyen, Tuan Dung; Kalairaj, Manivannan Sivaperuman; Hema, Vishnu Mani; Cai, Catherine Jiayi; Huang, Hui; Lim, Chwee Ming; Ren, Hongliang (Frontiers in Robotics and AI, 2021)
Swabbing tests have proved to be an effective method of diagnosis for a wide range of diseases. Potential occupational health hazards and reliance on healthcare workers during traditional swabbing procedures can be mitigated by self-administered swabs. Hence, we report possible methods to apply closed kinematic chain theory to develop a self-administered viral swab to collect respiratory specimens. The proposed sensorized swab models utilizing hollow polypropylene tubes possess mechanical compliance, simple construction, and inexpensive components. In detail, the adaptation of the slider-crank mechanism combined with concepts of a deployable telescopic tubular mechanical system is explored through four different oral swab designs. A closed kinematic chain on suitable material to create a developable surface allows the translation of simple two-dimensional motion into more complex multi-dimensional motion. These foldable telescopic straws with multiple kirigami cuts minimize components involved in the system as the characteristics are built directly into the material. Further, it offers a possibility to include soft stretchable sensors for realtime performance monitoring. A variety of features were constructed and tested using the concepts above, including (i) tongue depressor and cough/gag reflex deflector; (ii) changing the position and orientation of the oral swab when sample collection is in the process; (iii) protective cover for the swabbing bud; (iv) a combination of the features mentioned above.